Infections in gynecology and obstetrics. Pelviperitonitis acute salpingitis endometritis. - Maradiegue Méndez, Eduardo (2015)
Pelviperitonitis acute salpingitis endometritis (ESP), previously called acute pelvic inflammatory disease, occurs in the menstrual phase and preferably during the 3rd and 4th. decade of life, which is the fundamental stage of sexual activity; rarely it is diagnosed in women not sexually active.